APPLICATION OF THE DEMONSTRATION METHOD TO TRAIN FINE MOTOR SKILLS FOR CHILDREN AGED 5-6 YEARS AT PERMATA BUNDA KINDERGARTEN, SURABAYA - Ilmawati, Zakia Tiffani; Setyowati, Sri (Lentera : Journal of Gender and Children Studies, 2023)
The demonstration method is a teaching method using demonstrations to clarify an understanding or to show how a particular formation process works. This research is descriptive qualitative research. This case study descriptive research method aims to learn more and describe the conditions that occur in the field. This research is conduct at Permata Bunda Kindergarten in Surabaya. This research aims to describe the results of applying the demonstration method to the fine motor development of children aged 5-6 years at Permata Bunda Kindergarten Surabaya. Based on the results of the research conducted, it can be concluded that the reduction in the application of the riot method can create a learning atmosphere that is not conducive, so it greatly affects children's skills. The impact of the method on children can be seen from the results of learning activities. The results of the study stated that the application of the demonstration method provided by the teacher which included planning, processes, and activities to train fine motor skills in children aged 5-6 years at Permata Bunda Kindergarten Surabaya requires a bonded unity between the various elements. Keywords: Demonstration Method; Fine Motor